The Effect of Covid-19 Pandemic on Increasing Rice Tiwul Business Income Using System Dynamic Approach - Titus Kristanto; Dewi Rahmawati; Ayu Endah Wahyuni; Muhammad Nasrullah; Reza Arindra Fadillah; Amanda Amalia (Future Science, 2021)
In industry 4.0, the development of the food business is growing rapidly with the support of technology. His food business is tiwul rice. The establishment of the Nasi Tiwul SBR business began in March 2020 (coinciding with the beginning of the Covid-19 pandemic in Indonesia). The problem that occurs in Nasi Tiwul SBR is increasing the in-come of tiwul rice during the Covid-19 pandemic. The approach taken in this research is to use a dynamic system approach. The purpose of using a dynamic system approach is to provide feedback on the behavior of the systems involved in the research, especially the owner of the tiwul rice business. The result of this research is to increase the business income of tiwul rice and increase the market share of tiwul rice products.